Relationship between upper extremity fat mass and race time in triathlete - Cetin, E.; Bilgin, U.; Colak, M.; Yarim, I.; Taskin, H. (Turkish Journal of Sport and Exercise, 2017)
This study was conducted to investigate the effect of upper extremity fat ratio on triathletes` the race time. 43 volunteer athletes who participated in the 9th World University Triathlon Championship ((17 women - 26 men), age 22.30 ± 2.42 years, height 172.76 ± 16.08 cm, body weight 64.79 ± 9.93 kg)) participated in the study. Segmental analysis was performed by Tanita BC 418 Body Composition Analyzer before the race, on an empty stomach and with shorts and T-shirt. At 40 ° C air temperature, athletes firstly swam for 1.5 km, which was followed by cycling on 40 km track and finally 10 kilometers track run. SPSS 16.0 statistical software was utilized for data calculation and evaluation. According to the normality test results; Pearson correlation analysis was used to explain the relationship between the measurements and linear regression analysis was utilized to determine the effect of fat ratio on race time. This study in which the effect of upper extremity fat ratio on race time was examined, revealed that upper extremity segmental analysis has no significant effect on swimming time in triathlon (p >0.05). In addition; upper extremity fat mass has no significant effect on jogging, cycling and total race time either (p>0.05). Fat percentage is determined to have a significant relationship in positive manner with jogging (r = 0.382), cycling (r = 0.370), and total race time (r = 0.387) at p <0.05 level. Upper extremity lean mass and muscle mass are found to have a significant relationship in negative manner respectively with jogging (r = -0.475, r = -0.472), cycling (r = -0.738, r = -0.735) and total race time (r = -0.664, r = -0.661) at p <0.001 level. As a result, it was observed that the upper extremity fat mass is not associated with jogging, cycling, swimming and total race time, on the other hand upper extremity muscle and lean mass are found to be more effective on race time as compared to fat percentage. As the upper extremity, lean mass and muscle mass increases, total race time of athletes shortens and accordingly their performance are likely to be affected in a positive manner.